THE INFLUENCE OF ATTITUDES, SUBJECTIVE NORMS AND BEHAVIORAL CONTROL ON CONSUMERS' INTENTION TO REPURCHASE HERBALIFE PRODUCTS IN SEMARANG CITY - Sholikhah, Siti; Suwardi, Suwardi (Economics and Business International Conference Proceeding, 2024)
This research aims to examine the influence of attitude, subjective norms, and behavioral control on the repurchase intention of Herbalife product consumers in Semarang City. This study employs a quantitative approach. The research object in this study is consumers of Herbalife products in Serang City, with a total of 100 individuals selected as respondents. Data were collected from questionnaires distributed to customers consuming Herbalife shakes in Semarang City through Google Forms. The analysis technique was carried out by hypothesis testing using t-tests, F tests, and tests of the coefficient of determination, validity tests, reliability tests, normality tests, multicollinearity tests, and heteroscedasticity tests. This research was processed using SPSS 22. The results of the study indicate that attitude has a positive and significant effect on repurchase intention, subjective norms have a positive and significant effect on repurchase intention, and behavioral control has a positive and significant effect on repurchase intention. Furthermore, attitude, subjective norms, and behavioral control simultaneously have a positive and significant impact on the repurchase intention of Herbalife product consumers in Semarang City.